2020
DOI: 10.1177/0954405420911275
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the microstructure and machinability in machining Al–(5–25) wt% Si alloys

Abstract: The machinability of the Al–Si alloys becomes worse with the Si content increasing. This article explored the influence of Si content on the machinability including cutting forces and chip breakability in machining the Al–Si alloys. The change in machinability of the Al–Si alloys with different Si content attributes to the evolution of microstructure. The cutting forces when cutting hypoeutectic Al–Si alloys are higher than the hypereutectic alloys because only Mg2Si ( β-phase) precipitations are formed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These alloys are used in a variety of automotive and aerospace components due to their good castability and fluidity properties, as well as a combination of high ductility, high specific strength, high corrosion and wear resistance. [1][2][3] A356 (Al-7Si), a hypo-eutectic alloy from the Al-Si-Mg system, is used widely in recent decades for vehicularengine block/head applications due to its excellent casting ability, high strength/weight ratio and excellent heat-treatable characteristics. 4,5 Cooling rate, modification and heat treatment are the three factors that influence the silicon morphology.…”
Section: Introductionmentioning
confidence: 99%
“…These alloys are used in a variety of automotive and aerospace components due to their good castability and fluidity properties, as well as a combination of high ductility, high specific strength, high corrosion and wear resistance. [1][2][3] A356 (Al-7Si), a hypo-eutectic alloy from the Al-Si-Mg system, is used widely in recent decades for vehicularengine block/head applications due to its excellent casting ability, high strength/weight ratio and excellent heat-treatable characteristics. 4,5 Cooling rate, modification and heat treatment are the three factors that influence the silicon morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Tool wear and Ra increase due to high amount of hard Si particles, 15 Basavakumar et al 16 and Bayraktar and Afyon 17 determined that built up edge (BUE) consisted of by welding the material to the cutting edge due to friction and pressure between the cutting tool and the workpiece. Zhang et al 18 found that the cutting stability of Al-Si based alloys increased with Si content in the range of 12wt.%–18wt.% by weight and decreased by 25 wt.% Si by weight, and that the chip breakability increased with increasing of Si content and cutting speed. Kamiya et al observed that the chip breakability and surface quality increased due to the increase in Si content in eutectic compositions, while tool life decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, machining is essential in several cases. Some researchers have experimentally investigated the machinability of Al-Si alloys [12][13][14]. However, the effect of machinability on the surface characteristics by varying the percentage of Si in Al-Si automotive alloys is not fully understood yet specially in milling operation.…”
Section: Introductionmentioning
confidence: 99%